The Biological and Nutraceutical Properties of Methanolic Extract of Medicago sativa in Iran - Ebrahim Salimi-Sabour; Mohammad Amrollahi-Sharifabadi; Eisa Kaveh Vernousfaderani; Kamran Rezaei; Mohammad Kamalpour; Sahar Abdelaziz (International Journal of Nutrition Sciences)
Background: Medicago sativa has been used as food by both humans and animals. However, its nutraceutical properties have yet to be clarified, and thus, the present study aimed to evaluate the biological properties of M. sativa.Methods: Total phenolic and flavonoid contents of the methanolic extract of M. sativa were determined using Folin-Ciocalteu colorimetric and Woisky-Salatino methods. The antioxidant and antimicrobial activities of this plant were examined using in vitro assays. The anti-malarial and anti-platelet aggregation activities were evaluated by heme detoxification and turbidometric methods, respectively. Cytotoxicity and brine shrimp lethality assays were used for toxicological evaluations.Results: M. sativa methanolic extract had 38.7±0.57 mg of gallic acid equivalents/g extract and 27.6±0.31 mg rutin equivalents/g extract concentration of phenolic and flavonoid contents. The strongest antibacterial activity was against Staphylococcus aureus and Salmonella enterica with Minimum Inhibitory Concentration (MIC) of 62.5 mg/mL, and 62.5 mg/mL, respectively. The extract showed antioxidant activity with half-maximal inhibitory concentration (IC50) of 179.1 μg/m. Regarding the anti-platelet activity, the extract with a concentration of 20 mg/mL inhibited the arachidonic acid pathway by 23.70%. The brine shrimp lethality assay results showed that LC50 of M. sativa extract was 17.62074 μg/mL; while the cytotoxicity assay revealed that the extract at concentration of 10000 μg/mL was toxic for human dermal fibroblasts and corneal epithelial cells.Conclusion: Our study elucidated the antibacterial, antioxidant, and antiplatelet aggregation properties of the methanolic extract of M. sativa.